INCREASING THE STUDENTS’ SKILL IN READING NARRATIVE TEXT BY USING KNOW-WANT-LEARNED STRATEGY AT THE EIGHT GRADE STUDENTS OF JUNIOR HIGH SCHOOL 3 PALEMBANG - Etty Pratiwi; Dewi Kartika Sari (Esteem Journal of English Education Study Programme, 2021)
The aim of this research was to increase the students’ skill in reading narrative text by using Know-Want-Learned strategy at the eight grade students of Junior High School 3 Palembang. This research of this study was conducted by using classroom action research. The data used in this research are the result the pre-test to know the improvement of students in reading narrative text. The mean of the pre-test was 64,5. The mean of the first cycle was 84,85, it indicated that the scores and the mean in first cycle were better than the pre-test. The percentage of students who got point 75 or more there was also grew up. In the pre-test, there was 10 students (25%) who passed or got score up to 75. In the post-test of cycle I the students who got point 75 or more there was 40 (100%) and the increasing was about 75%. In other words, the students’ skill in reading narrative text improved and became well in the first meeting to the next meeting. For the hyphothesis testing used t-test formula from the compilation, it could be seen that coefficient of it could be seen that coefficient of tobserved (16,72) > ttable (0,316). Thus, alternative hyphothesis (Ha) could be received. Based on the research, It could be get that using Know-Want-Learned (KWL) Strategy could increase the students’ skill in reading narrative text.